PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADTOGETHER (NHT) TERHADAP MATERI PENCACAHAN SISWA KELAS XI IPS SMA NEGERI MANOKWARI - Beslar, Serlani; Siregar, Tiurlina (Jurnal Ilmu Pendidikan Indonesia, 2015)
This research aims to determine the effect of Cooperative learning model type Numbered Head Together (NHT) on learning Mathematics toward studentsâ effectiveness and learning outcomes. The method used in this study is an experimental method. The data is analyzed by using an undemanding linear regression model. The result of this learning model (x) does not give effect to student activity (Y1). The computation on learning the rules of permutation enumeration has shown significantly by the count value >0,05 (Level of 5 %), the regression equation Y1=70.637 + 0.069 X. The learning model (X) gives the effect on learning outcomes (Y2)by thesignificance count < significance table (level of 5%), 0.016